Feto-maternal outcome among pregnant females in block Hazratbal of district Srinagar, Jammu and Kashmir: a prospective longitudinal study - Rather, Rouf Hussain; Nazir, Umar; Samreen, Sheema; Itoo, Mohammad Saleem (International Journal Of Community Medicine And Public Health, 2017)
Background: Pregnancy is a normal physiological state which a woman experiences at some point of her life. During pregnancy a woman may develop complications which pose a risk to both maternal and fetal health. Caesarean section is a surgical procedure in which incision is made through a mother’s abdomen and uterus to deliver one or more babies. The aim and objective of the study was to describe feto-maternal outcome among the study population in block Hazratbal, Srinagar. Methods: A community based longitudinal study was conducted in block Hazratbal (District Srinagar) for a period of 18 months. All the pregnant females attending the antenatal clinic at the subcenters and PHCs were included in the study and assessed for eligibility. The pregnant women enrolled in the study were examined again around 30 weeks, 37 weeks and once in postnatal period. Results: Only 2.6% were home deliveries. More than two-thirds (71.7%) of the study subjects delivered by LSCS and less than 2% of the study subjects delivered twins. Out of 391 children born 2 were born dead and 55.2% were of male gender. The mean gestational age at delivery was 38.56 weeks and the mean birth weight of neonates was 2.731 kg with only 4.9% LBW neonates. Conclusions: The percentage of institutional deliveries was good (97.4%) and the proportion of twins and male babies were within expected limits. The prevalence of LBW babies was only 4.9 against the national average of 28%. But the 71.7% caesarean section rate is too high and needs immediate attention by policy makers. Moreover both healthcare professional as well as general population need to be educated about the disadvantages of unnecessary caesarian sections.